Relationship of Metacognitive Awareness and Family Support to Online Learning - Khoirunnisa, Khoirunnisa; Huzaifah, Siti; Madang, Kodri; Tibrani, Masagus Muhammad (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2022)
Many factors are related to student learning outcomes in bold learning, including metacognitive awareness and family support. This correlational study aims to determine the relationship between metacognitive awareness and family support on the learning outcomes of students of class XI MIA (Mathematics and Natural Sciences) SMA Negeri 3 Martapura on the digestive system material in 2021/2022. The population in this study were all class XI MIA SMA Negeri 3 Martapura which consisted of 91 students with the number of samples tested amounting to 73 samples of this study were determined randomly. Method of data collection using a questionnaire and distributed via google form. The instrument used is developed by the author and has been validated by expert lecturer. Questionnaires were given to determine metacognitive and family relationships and were given multiple choices to determine learning outcomes. The results showed that there was a positive but low correlation (r = 0.228) between metacognitive awareness and courageous learning outcomes. There is a negative correlation (r = -0.053) between family support and courageous learning outcomes (Y = 12.917+0.152 X1 - 0.108 X2) which indicates a low relationship between metacognitive awareness and family support on courageous learning outcomes. The implication of this research is that metacognitive awareness and family support are not closely related to learning outcomes and there are many other factors that have a closer relationship